Muslim Solidarity with Palestine whilst Living on Stolen Land: The politics of Ramadan in Australia - Randa Abdel-Fattah (ReOrient)
This paper contextualises Muslim celebrations within a neoliberal understanding of politics and the consequent erasure of Indigenous identity. It traces the overlap of spectacles of Israeli brutality against Palestinians during Ramadan with official Ramadan and Eid celebrations in Australia when the Islamic concept of “ummah” is invoked to mobilise Muslim solidarity with Palestine. Using Foucauldian discourse analysis, and drawing on Critical Indigenous studies, Settler Colonial Studies, and Critical Muslim Studies, I analyse the discursive repertoires mobilised by Muslim “representatives” in their Ramadan/Eid engagements with the Australian settler-colonial state. I outline how respectability politics and liberal multicultural agendas pursued by Muslim community leadership legitimate and reproduce settler-colonial relations of power and demonstrate how this undermines a praxis of ummah as potential clarion call to decolonial, anti-imperial struggle both here on stolen land and in solidarity with Palestinians.